Odontogenic Keratocyst: A Case Report Emphasizing on Root Canal Treatment after Surgical Intervention - Tarallo, Alessandra Manchini Cardoso; Matos, Felipe de Souza; Souza, Valdirene Ferreira de; Paranhos, Luiz Renato; Herval, Ãlex Moreira; Valera, Marcia Carneiro; Carvalho, ClÃ¡udio Antonio Talge (Iranian Endodontic Journal, 2019)
This article presents a case of odontogenic Keratocyst (OKC) located in the mandible, involving teeth 36 to 45, with significant loss of alveolar bone and aseptic pulp necrosis, emphasizing on root canal treatment after surgical intervention. Orthopantomogram and computed tomography examinations revealed an extensive, well-defined, and multilocular radiolucent lesion. Histopathological examination after incisional biopsy confirmed OKC, which was removed completely with enucleation and curettage, followed by the endodontic treatments of teeth 36 to 45 using reciprocating nickel-titanium files (Reciproc) in a single session. Afterwards, teeth 33 to 36 underwent apical surgery to create an appropriate bone development. Panoramic radiographic images showed bone formation and no sign of recurrence after one-year follow-up. In conclusion, this surgical approach, combined with the endodontic treatments of the teeth involved in the lesion, was effective for the management of OKC, promoting injury regression and preservation of the natural teeth. Keywords: Dental Pulp Necrosis; Enucleation; Odontogenic Cysts; Odontogenic Keratocyst; Root Canal Therapy